2019
DOI: 10.1016/j.jpainsymman.2018.09.020
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Training in Symptom Management in Palliative Care Within Postgraduate Medical Curriculums

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 61 publications
2
17
0
1
Order By: Relevance
“…thinking in specific situations. Patient-centered care education is a priority at all levels of education [37], and almost all studies have shown that education can contribute to improvements in learners' attitudes, knowledge, skills, and behavior [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…thinking in specific situations. Patient-centered care education is a priority at all levels of education [37], and almost all studies have shown that education can contribute to improvements in learners' attitudes, knowledge, skills, and behavior [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Turrillas et al [68] argue that the most effective training method should be tailored to the environment and context. A re-piloting of a different training program will be developed, considering in particular the bed side component.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not collect data directly from healthcare professionals, it is plausible that healthcare professionals' fears and misinformation about opioids may have contributed to such patient experiences, since misconceptions about the essential role of opioids in cancer pain relief have been described as a significant barrier to effective pain management in many resource-limited settings [4,18,22]. Education for clinicians about the safe use of opioids can improve pain management for patients, and the Lancet Commission proposed basic mandatory training for all healthcare providers [2,23,24]. Implementation of these strategies should be considered by humanitarian organizations to improve pain management [6].…”
Section: Painmentioning
confidence: 99%